Resveratrol Prevents Cognitive Impairment in Type 2 Diabetic Mice by Upregulating Nrf2 Expression and Transcriptional Level [Corrigendum] - Wang X (Dove Medical Press, 2020)
Wang X, Fang H, Xu G, et al. Diabetes Metab Syndr Obes. 2020;13:1061–1075.The authors have advised the affiliations listed for Hui Fang and the correspondence address on page 1061 are incorrect. The text “Hui Fang2” in the author list should read “Hui Fang1,2”. The correspondence address is as follows.Correspondence: Hui FangDepartment of Internal Medicine, Hebei Medical University,361 Zhongshan East Road, Shijiazhuang, Hebei 050017,People’s Republic of ChinaTel +86-13831581838Fax +8631186266193Email fanghui2018@126.comThe authors apologize for these errors.Read the original article